2010
DOI: 10.4269/ajtmh.2010.09-0345
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Infection with Visceral Leishmaniasis in a Disease-Endemic Area in Bihar, India

Abstract: Abstract. A prospective study was carried out in a cohort of 355 persons in a leishmaniasis-endemic village of the Patna District in Bihar, India, to determine the prevalence of asymptomatic persons and rate of progression to symptomatic visceral leishmaniasis (VL) cases. At baseline screening, 50 persons were positive for leishmaniasis by any of the three tests (rK39 strip test, direct agglutination test, and polymerase chain reaction) used. Point prevalence of asymptomatic VL was 110 per 1,000 persons and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 19 publications
7
85
0
Order By: Relevance
“…Additionally, asymptomatic individuals can still act as a reservoir for parasite transmission. Topno and others 27 found that 13% of neighbors of VL cases were seropositive for leishmaniasis without showing symptoms. 15,28 In South Asia, it has been reported that living close to a previous case of VL strongly increases the risk of contracting the disease as well as acquiring a subclinical infection.…”
Section: Resultsmentioning
confidence: 94%
“…Additionally, asymptomatic individuals can still act as a reservoir for parasite transmission. Topno and others 27 found that 13% of neighbors of VL cases were seropositive for leishmaniasis without showing symptoms. 15,28 In South Asia, it has been reported that living close to a previous case of VL strongly increases the risk of contracting the disease as well as acquiring a subclinical infection.…”
Section: Resultsmentioning
confidence: 94%
“…35 However, our study population was asymptomatic and higher positivity rates have been reported for DAT versus rK39-ICT when these methods are used to assess asymptomatic infection in other VL-endemic areas. 7 Given that performance of a serologic test can depend on the stage of the disease/infection, the lower performance of rK39-ICT can be explained by its ability to detect antibody response against only a single antigen (rK39), whereas the DAT relies on detection of antibodies against a wide range of Leishmania antigens (whole freeze-dried promastigote). 36 Another explanation is based on the nature of the tests.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In stable disease-endemic areas, clinical disease appears only in a fraction of those infected, and another fraction will not develop the disease and remain asymptomatic. 7 The prevalence of asymptomatic infection is different between and within different disease-endemic countries, and the number of asymptomatic infections usually exceeds the number of symptomatic infections, although this ratio can vary from 0.4:1 to 50:1. 2 Visualization of parasite amastigotes by microscopic examination of bone marrow, spleen, or lymph node aspirates has been the gold standard method of VL diagnosis for many years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29] The paucity of overt kalaazar cases in this community is unusual for anthroponotic transmission based on epidemiological studies in India and Bangladesh. [30][31][32] The explanation is not clear, but could include the possibility of transmission from asymptomatically infected humans, or an unidentified animal reservoir. None of the dogs studied in the Trashigang canine shelter showed any marker of Leishmania infection, but the sample size was too small to yield a definitive answer regarding a potential canine reservoir role.…”
Section: Discussionmentioning
confidence: 99%